Theory of Planned Behavior pada Perilaku Anti Korupsi Mahasiswa STKIP PGRI Situbondo - Noervadila, Irma; Seituni, Siti (LPPM Press, 2023)
The main objectives of this research is to build and increase awareness so that there will be changes in behavior among students regarding anti-corruption behavior. This research is a qualitative and quantitative descriptive research with the subject of this research being the first semester economics class of the economics education study program with a sample size of 35 students in this research, namely 35 respondents. The measurement results obtained are control belief variables, normative beliefs, behavioral beliefs and behavioral variables. Of the four indicators above, the average agree and strongly agree was 57.76%. So that the impact of instilling values in this anti-corruption course is effective in the STKIP PGRI Situbondo campus environment and can be used as a solution to maintain behavior in society to avoid corruption. Preventing acts of corruption among students can also be prevented with positive affirmations during lectures. This is the first step so that students can control themselves through positive input or affirmation by lecturers who teach anti-corruption education courses. One of the things that is very important in an action is control beliefs which is an indicator in this research.